2018
DOI: 10.1016/j.bbmt.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Minimal Residual Disease Monitoring in Patients with t(16;21) Acute Myelogenous Leukemia Undergoing Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Patients with t(16;21) acute myelogenous leukemia (AML) who receive chemotherapy have poor outcomes. The treatment efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) must be identified, and the usefulness of minimal residual disease (MRD) monitoring requires evaluation. Fourteen consecutive patients with t(16;21) AML undergoing allo-HSCT at our institution were included in this study. Translocation liposarcoma- ETS-related gene (TLS-ERG) transcript levels were serially monitored for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In comparison, Pan et al 1 conducted a retrospective study of patients with FUS::ERG AML and found that HSCT could improve OS but not leukemia-free survival. Alternatively, Qin et al 4 demonstrated that 5 of 11 patients with AML harboring FUS::ERG who underwent haploidentical transplantation were alive without relapse. The heterogeneity of the chemotherapy regimen and supportive care, as well as the small sample size in each study, might account for such inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, Pan et al 1 conducted a retrospective study of patients with FUS::ERG AML and found that HSCT could improve OS but not leukemia-free survival. Alternatively, Qin et al 4 demonstrated that 5 of 11 patients with AML harboring FUS::ERG who underwent haploidentical transplantation were alive without relapse. The heterogeneity of the chemotherapy regimen and supportive care, as well as the small sample size in each study, might account for such inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that traditional chemotherapy failed to eradicate leukemic cells in these patients, which might partially explain the limited effect of HSCT in our study. 4 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients also monitored MRD at the 1, 2, 3, 4.5, 6, 9, and 12 month after preemptive IFN-α treatment and at 6-month intervals thereafter. MRD-positivity was defined when a single BM sample tested positive for leukemia-associated aberrant immune phenotypes (LAIPs) and/or different from normal (DfN) by multiparameter flow cytometry (MFC) 22 or one of the following molecular markers: RUNX1-RUNX1T1 31 , CBFβ-MYH11 32 , KMT2A 33,34 , TLS-ERG 35 , DEK-NUP214 36 , BCR-ABL 37 , or NPM1 mutations A, B, and D 38 using realtime quantitative polymerase chain reaction (PCR) (Supplementary Methods).…”
Section: Mrd Monitoringmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an efficient therapy that contains the potential to cure hematologic malignancies. Although the incidence of post-transplant relapse is now being lowered by monitoring minimal residual disease [ 1 ], creating risk-based preventative strategies [ 2 ], and optimizing donor lymphocyte infusions (DLI) [ 3 ], relapse continues to be the leading contributory factor to death in individuals following transplantation. Furthermore, because the preconditioning of allo-HSCT leaves the body in a condition of extreme immunodeficiency and years of B- and T-lymphocytopenia after transplantation [ 4 6 ], infectious complications remain a difficult challenge to deal with following allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%